Impacts of a partially connected wastewater treatment plant on the water quality of stormwater drains used as an irrigation source - Samaraweera, S. A. P. T.; Najim, M. M. M.; Alotaibi, Bader Alhafi; Traore, Abou (Frontiers in Environmental Science, 2024)
Urban stormwater drains in Kurunegala city collect runoff and untreated wastewater, leading to public health problems. Greater Kurunegala Sewage Treatment Plant (GKSTP) was commissioned in 2018 and currently operates at 73% of its capacity to combat public health issues. This study assessed the water quality of canals, comparing it with standards and pre-GKSTP conditions.Water samples were collected from seven sites during dry and wet seasons, and physicochemical parameters were measured. The data underwent spatial and temporal analysis using the General Linear Model (GLM).Additionally, cluster analysis and Distance-based Redundancy Analysis were employed. The Water Quality Index (WQI) was employed to evaluate the effectiveness of the treatment plant. The study revealed significant spatial and temporal variations in physicochemical parameters along the canals (p<0.05, GLM), with higher pollution levels during wet months. The WQI improved from 35 (2005) to 49 at present, indicating enhanced water quality (p<0.05, ANOVA), although it remains unsatisfactory. This study provides novel insights into the limitations of conventional wastewater treatment practices, demonstrating that merely treating wastewater and discharging it back into canals is insufficient. The research underscores the importance of rethinking treated wastewater reuse in achieving multiple SDGs. This approach offers a pragmatic path forward for enhancing water security and environmental sustainability globally.